Special Needs Handbook : Identifying and supporting needs, activities covering early learning goals, working with parents - Mortimer, Hannah (Leamington Spa : Scholastic, 2002)
Dr Hannah Mortimer is a chartered educational psychologist who has written extensively about special needs issues. This book is designed to be used alongside the activity books in this series.
Includes bibliographical references (p. 62-63).
Keywords: Special education -- Great Britain -- Handbooks, manuals, etc; Early childhood education -- Great Britain -- Handbooks, manuals, etc; Education